Efektifitas Muhadhoroh Terhadap Peningkatan Kemampuan Public Speaking Santri (Pondok Pesantren Markazul Quran Pamijahan Kabupaten Bogor Barat) - Adam Ichsan Putra (KOLONI, 2024)
As a speaking skill, Public Speaking has been and will always be a rudimentary need for every human being as a social creature, especially for students who will get along directly into society in the future. This research aims to find out whether Muhadhoroh is effective in improving the Public Speaking skills of students at the Markazul Quran Islamic Boarding School in Bogor, and to find out what solutions are implemented by supervisors in Muhadhoroh activities to improve the Public Speaking skills of students. This research used qualitative method, where the researcher conducted interviews with several informants at the Markazul Quran Islamic Boarding School in Bogor, as well as conducting observations and documentation. The research findings revealed that muhadhoroh activity at the Markazul Qur'an Islamic boarding school is effective in improving students' public speaking skills. The obstacles faced by muhadharah supervisors are: Lack of interest among students in participating in muhadharah activities, friends who are not yet supportive, some students feel afraid of being appointed as its officers. Muhadharah activity at the Markazul Qur'an Islamic Boarding School has the main aim of developing students' public speaking skills, providing provisions for speaking in public, and increasing their self-confidence. In the process, the students faced initial challenges but became accustomed to it over time, so that this activity proved effective in achieving its goals. Muhadhoroh supervisors provide solutions for students to be able to participate in this muhadhoroh as fully as possible.